In-Match and Out-Match Tactical Team-Based Shoot Game Screen and Network Performances Analysis (Case Study: East Jakarta, Indonesia) - Akbar, Andi Muhammad Imam; Wulandari, Dewi Arianti; Solihin, Unang; Wandy, Wandy (INTEK : Jurnal Informatika dan Teknologi Informasi, 2025)
Online games have transformed the gaming landscape by connecting players from around the globe in immersive and interactive virtual environments. First-person shooters have gained immense popularity among the various genres due to their fast-paced action, strategic gameplay, and realistic graphics. The Sony PlayStation 5 (PS5) has revolutionized the gaming landscape since its launch, establishing itself as a dominant force in the global market. This research aimed to find screen performance (in FPS) and network performance (in ping) during in-match and out-of-match while playing the game on the PS5 gaming console. This research applied a quantitative method, primary data, and a descriptive approach. The analysis of in-match network ping, with an average of 22.7-5.78 ms, reveals a relatively stable connection with some variability. Although occasional spikes up to 32 ms may cause brief delays, the overall network performance is satisfactory for typical internet usage. Conversely, the out-of-match network ping demonstrates exceptional stability, with an average of 24.43-0.82 ms, indicating minimal latency variation and ensuring a smooth experience for various online activities. The frame rate analysis on the PS5 showcases a consistent FPS of 60, reflecting a rock-solid performance free from stuttering or frame drops, essential for both casual and competitive gaming.